Human acute poisoning incidents associated with neonicotinoid pesticides in the U.S. Incident Data System (IDS) database from 2018-2022 - frequency and severity show public health risks, regulatory failures - Jennifer B. Sass; Daniel Raichel (BMC, 2024)
Abstract Background Neonicotinoid pesticides ('neonics') - imidacloprid, thiamethoxam, clothianidin, acetamiprid, dinotefuran-are the most widely used class of insecticides in the world. They have a neurotoxic mechanism of action, similar to nicotine. They are detected in food, waterways, tap water, and breast milk. Methods We make use of the non-occupational human pesticide poisoning reports in the U.S. Environmental Protection Agency (EPA) online Incident Data System (IDS). The data set contains individual incidents, and incidents aggregated and submitted in bulk to EPA. IDS reports are predominantly self-reported information of varying and often low level of detail and are not routinely validated or verified by EPA. Results We reviewed 842 non-occupational human poisoning incidents associated with neonics in the IDS from 2018 through 2022. There are four human fatality reports, two associated with clothianidin and two with acetamiprid. Major illnesses such as seizures were reported in several cases, including with dinotefuran cockroach bait product, and an imidacloprid lawn product. Moderate poisonings make up 88% of the total poisonings (740 of 842), with most of those associated with imidacloprid (547 incidents) or dinotefuran (102 incidents). Common reported symptoms classified as moderate often included two or more of the following: headaches; dizziness; lethargy; eye or throat irritation; skin itching and rash; chemical burns and skin peeling; face swelling; muscle weakness or tremors; vomiting; diarrhea; pain and tightness in chest; open sores; and general pain. These incidents stem mainly from residential uses, such as lawn and garden insect repellents, home pest treatments for bed bugs or roaches, and products used to treat pets for fleas and ticks. Conclusion Given the evidence of neurotoxicity, EPA should use its legal authority to cancel unsafe products and unnecessary uses - including from seed treatments, and residential pet and lawncare products - to prevent further human suffering.